(untitled) (Revista Apotheke, 2024)
This article aims to discuss initial training based on experiences in the subject of Supervised Curricular Internship IV in the Degree in Visual Arts at the University of the State of Santa Catarina (UDESC). Bringing teaching identity as a central concept (Pimenta, 1999), the specific spaces for artistic practices within schools and their influence on teacher training are discussed, as well as the project Between the lines of teacher training as a possibility of poetic reflection on the building and rebuilding oneself as a teacher. In this context, the authors Freire (1997) and hooks (2020) are addressed by weaving a dialogue with the perspective of an engaged pedagogy.